Airbreathing hypersonic propulsion : an introduction - Bruno, Claudio (Springer, 2023)
This book details science of hypersonics especially focusing on propulsion aspects such as supersonic combustion ramjets and their applications, and also includes lift and drag in hypersonic flight and their mathematical and physical explanation. It provides charts and data from hypersonic testing and measurements from actual vehicles and engines built in the past. Criteria to dimension hypersonic powered and unpowered vehicles (gliders) based on fundamental fluid dynamics and backed by flight testing; criteria to preliminary sizing vehicles and preliminary dimensioning of supersonic combustors are introduced. The book will serve better theoretical understanding of drag, lift and how to apply them to the design of hypersonic vehicles, as well as data to size vehicles and supersonic combustion ramjet (SCRJ) systems. This book will be a useful reference for researchers and designers in hypersonic vehicles but also second or third-year graduate students.
Keywords: Jet propulsion.; Airplanes -- Ramjet engines -- Combustion.; Space vehicles -- Propulsion systems.; elektronické knihy; electronic books